The 823rd hit - Scaletta, Kurtis. (Laura Ann); Wight, Eric 1974- 1978- 1906-1998. (New York Amulet Books, 2012)
To keep Teddy "Bear" Larrabee happy and slugging, Chad the bat boy has to figure out what a crabby fan would be willing to trade for Teddy's lucky homerun ball.
Keywords: Baseball -- Fiction; Bat boys -- Fiction; Baseball cards -- Fiction; Stories